If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -2x = -8x + 10 Reorder the terms: 16 + -2x = 10 + -8x Solving 16 + -2x = 10 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 16 + -2x + 8x = 10 + -8x + 8x Combine like terms: -2x + 8x = 6x 16 + 6x = 10 + -8x + 8x Combine like terms: -8x + 8x = 0 16 + 6x = 10 + 0 16 + 6x = 10 Add '-16' to each side of the equation. 16 + -16 + 6x = 10 + -16 Combine like terms: 16 + -16 = 0 0 + 6x = 10 + -16 6x = 10 + -16 Combine like terms: 10 + -16 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| (3x-1)(2x+2)= | | 12x-16=2x+14 | | 10x+3(2x+5)=5 | | 46+4x=6x+76 | | 28-3(4-x)=-2 | | 28-3(4-x)=-2 | | 28-3(4-x)=-2 | | 3x+25=40-17x | | -22-y=10 | | m^3+m^2+1=0 | | -7.5n+1.4=-6.1 | | 26+12f=50 | | 9y+7=0 | | (p^3-3p^2+5p)-(-4p^3-3p^2-8p)= | | g(2g+4)(g+2)=0 | | t+y=n | | 2x+3.9=7.7 | | p-21-21=3 | | 9x-6+4x+4=0 | | -x-10=-30 | | 25-3-3x=1 | | 6(3x-10)=9(2x+1) | | K+36=37 | | -2(n+3)=24 | | 5p+7-3p-2+6p= | | 24+6x=27 | | 7x-8y+3=5x-5y-9 | | 10x+4x=36 | | 53.90=1.1c | | 15=-16t^2+15 | | 15=-16t^2+15 | | 323.4=-13.2z |